Background differences of parental attributes: a case study of a preschool road safety education programme in Perak - Shahrimin, Mohamad Ibrani; Labulla, Sha Harudin; Koay, Saik Hua; Tai, Win Nie (Universiti Putra Malaysia Press, 2012)
This study was carried out to envisage and examine the plausible relationships of parental road safety knowledge, attitude and practice in relation to preschool children’s involvements in a road safety education programme in Perak, Malaysia. Three local preschools were selected for this purpose, in which the children underwent and an educational road safety programme. The respondents consisted of 100 parents of the pre-schoolers (note that two private and one government preschools were chosen through a purposive sampling method). Ethnicity was found to be significantly different compared to knowledge (χ2 = 16.272, p ≤ 0.05) and practice (χ2 = 10.635, p ≤ 0.05) scores. Chi-square analyses indicated that there is an association between parental road safety attitude and practice scores (χ2 = 21.444, p ≤ 0.05). In addition, the study also revealed that the attitude score varied significantly between the parents, while no significant difference was found between gender in knowledge and practice scores. However, this study also postulated that parental attitude and practice on road safety are moderately related to each other. Furthermore, the findings of the analyses also revealed certain gender inequalities, as the study indicated that female parents might have poorer knowledge and attitude scores. However, they appeared to be capable of showing more care and concern over road safety in relation to their preschool children’s safety and well being. Thus, it is hypothesized that road safety education ought to be inculcated among parents, together with their children, vis’ a vis’ to the current campaign on road safety education among young children.